Molecular characterization of infectious pancreatic necrosis virus strains isolated from the three types of salmonids farmed in Chile. Issue 1 (December 2017) - Manríquez, René; Vera, Tamara; Villalba, Melina; Mancilla, Alejandra; Vakharia, Vikram; Yañez, Alejandro; Cárcamo, Juan
Abstract Background The infectious pancreatic necrosis virus (IPNV) causes significant economic losses in Chilean salmon farming. For effective sanitary management, the IPNV strains present in Chile need to be fully studied, characterized, and constantly updated at the molecular level. Methods In this study, 36 Chilean IPNV isolates collected over 6 years (2006–2011) fromSalmo salar, Oncorhynchus mykiss, andOncorhynchus kisutch were genotypically characterized. Salmonid samples were obtained from freshwater, estuary, and seawater sources from central, southern, and the extreme-south of Chile (35° to 53°S). Results Sequence analysis of the VP2 gene classified 10 IPNV isolates as genogroup 1 and 26 as genogroup 5. Analyses indicated a preferential, but not obligate, relationship between genogroup 5 isolates andS. salar infection. Fifteen genogroup 5 and nine genogroup 1 isolates presented VP2 gene residues associated with high virulence (i.e. Thr, Ala, and Thr at positions 217, 221, and 247, respectively). Four genogroup 5 isolates presented an oddly long VP5 deduced amino acid sequence (29.6 kDa). Analysis of the VP2 amino acid motifs associated with clinical and subclinical infections identified the clinical fingerprint in only genogroup 5 isolates; in contrast, the genogroup 1 isolates presented sequences predominantly associated with the subclinical fingerprint. Predictive analysis of VP5 showed an absence of transmembrane domains and plasma membrane tropism signals. WebLogo analysis of the VP5 BH domains revealed high identities with the marine birnavirus Y-6 and Japanese IPNV strain E1-S. Sequence analysis for putative 25 kDa proteins, coded by the ORF between VP2 and VP4, exhibited three putative nuclear localization sequences and signals of mitochondrial tropism in two isolates. Conclusions This study provides important advances in updating the characterizations of IPNV strains present in Chile. The results from this study will help in identifying epidemiological links and generating specific biotechnological tools for controlling IPNV outbreaks in Chilean salmon farming.